RICE WAGE SYSTEM IN THE RICE MILLING PROCESS: PERSPECTIVE OF SHARIA CONTRACT PRINCIPLES - Jasri, Jasri; Istiqamah, Nurul; Rufaida, Erty Rospyana (Universitas Islam Negeri Mataram, 2024)
Rice milling, a critical stage in processing raw rice into consumable rice, often must fully comply with Sharia contractual principles, leading to multiple interpretations about its adherence to Sharia law. This study aims to analyze and formulate the Islamic law perspective on the contractual aspects of the paddy wage system in the rice milling process based on Sharia contract principles. The research method used is a descriptive method with a qualitative approach. Data were collected through observation, interview, and documentation. Data analysis in this research was conducted through three stages: data reduction, data presentation, and conclusion drawing. The results showed that the rice milling wage system paid by rice in Panakkukang Village, Pallangga Subdistrict, Gowa Regency, partially follows Islamic law when viewed from the principles of sharia contracts. Four of the seven principles of Sharia contracts are fulfilled, but three still need to be fully fulfilled. The Sharia contract principles that have been fulfilled are the principle of voluntarism/consensual, legal certainty/equality (al-musawah), honesty and truth (asl-sidq), and the principle of binding promises. The principles that have yet to be fully fulfilled are the principle of freedom of contract and justice (al-'adl), while the principle of writing (al-kitabah) still needs to be fulfilled.